THE INFLUENCE OF THINK PAIR SHARE STRATEGY AND LEARNING MOTIVATION TOWARDS READING COMPREHENSION ACHIEVEMENT TO THE EIGHTH GRADE STUDENTS OF SMPN 3 PALEMBANG - Linda Yani (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis research in concerned with the influence of think pair share strategy and learning motivation towards reading comprehension achievement of the eighth grade students of SMPN 3 Palembang. In this study 60 students of eighth grade students of SMPN 3 in the academic year 2017/2018 were chosen as samples by means of two stage random sampling. This study applied factorial research design. The data were collected by using questionnaire and t-test. The data were analyzed by using Paired Sample t-test, Independent Sample t-test, and Two Ways ANOVA. The results showed that, first, there was a significant difference in students’ reading comprehension taught using think pair share strategy. Second, there was not any significant difference in students’ reading comprehension taught by traditional teaching method. Third, there was significant difference in students’ reading comprehension students who had high and low learning motivation by using think pair share strategy and traditional teaching method. Lastly, there were not any significant interaction effects of think pair share strategyand learning motivation towards the students’ reading comprehension of SMPN 3 Palembang. In line with, think pair share strategy appropriate to the students who have high learning motivation and who have low learning motivation.Keywords: Think Pair Share Strategy, Traditional Teaching Method, Learning Motivation, Reading Comprehension.